Measurement of wind on the surface of Mars - Wilson, CF (2003)
The Martian atmosphere is of great scientific interest, both because of its similarity to Earth’s atmosphere, and because of its relevance to exploration of Mars. Although satellite instruments have provided a wealth of atmospheric data, they have provided little information about the atmospheric boundary layer. Conditions in the lowest few metres of the Martian atmosphere are perhaps the most directly interesting to humans, as this is the portion of our own atmosphere with which we have the most contact. In this thesis is described the design, calibration and operations planning for a new wind sensor for use on Mars. This sensor is lighter and smaller than previous Mars wind sensors. At the time of writing, the wind sensor is on its way to Mars as part of the science payload of Beagle 2, a small exobiology lander due to arrive in December 2003. The Beagle 2 wind sensor (B2WS) is a hot-film anemometer. Three platinum films are equally spaced around the surface of a vertical cylinder. A known current is dissipated in each film, heating the film 40-80°C above the ambient gas temperature. The film temperature is obtained by measuring its resistance. An effective heat transfer coefficient is then calculated for each film. A novel scheme has been developed which allows calculation of a wind vector from the differences between these heat transfer coefficients, rather than from their average. This makes the measured wind vector less prone to common-mode errors such as uncertainties in air temperature or sky temperature. The sensor was calibrated in a low density wind tunnel, optimised to provide stable winds of air or carbon dioxide at Martian pressures (5 – 10 mbar) and speeds (0.5 – 30 m/s). The flow field in the test section was calculated using analytical and finite element modelling techniques, and validated experimentally using a pitot probe. This facility’s stability and accuracy represent a significant improvement over previous calibration facilities. An analytical model of heat flow in the sensor has been developed in order to permit correction for conditions which may be encountered on Mars, but were not tested for in the wind tunnel. The wind sensor’s performance in a real Martian atmosphere is simulated using wind and temperature data from a previous Mars lander. The position of the wind sensor position at the end of Beagle 2's motorised arm allows several new possibilities for wind measurement on Mars that were unavailable in previous missions. The height of the wind and air temperature sensors can be adjusted to any height between 20 and 95 cm above the ground. The temperature sensor can be scanned horizontally and vertically above the lander to study convective updrafts above the heated lander. Planned operations sequences on Mars are discussed.